LOCAL HISTORY AS A BRIDGE FOR CONTEXTUALIZING HISTORY LEARNING: A LITERATURE REVIEW STUDY: A LITERATURE REVIEW STUDY - Ikhwanul Imam Mukhlis Safei; Syela Joe; Rhoma Dwi Aria Yuliantri (SOSIOEDUKASI, 2026)
History learning in Indonesia remains dominated by centralistic national narratives, marginalizing students' local historical experiences. This condition contributes to underdeveloped historical consciousness, particularly in its critical and genetic dimensions as theorized by Jörn Rüsen. This article aims to construct an argumentative framework explaining the role of local history contextualization as a conceptual bridge between national narrative abstractions and students' empirical realities. The study employs a systematic literature review (SLR) using narrative synthesis based on Popay et al.'s (2006) framework, analyzing a corpus of 15 articles retrieved from Google Scholar, Scopus, and DOAJ (2010–2025). The synthesis yields four main themes: (1) the dominance of national narratives and the reproduction of banking education; (2) local history as a pedagogical instrument beyond supplementary learning resources; (3) students' historical consciousness development within Rüsen's typology; and (4) contextualization as a conceptual bridge between Freire's critical pedagogy and Rüsen's historical consciousness. Findings indicate that local history-based learning can propel students from traditional and exemplary consciousness toward critical and genetic types, while repositioning them from passive recipients to active historical subjects. Nevertheless, the success of such contextualization requires structural support, including curriculum flexibility and the adequate provision of locally grounded learning materials.